Budaya Politik Lokal Dalam Pelaksanaan Pemilu Di Nagori Urung Panei Kecamatan Purba Kabupaten Simalungun - Tri Mei Rosalya Purba; Julia Ivanna (Universitas Sains dan Teknologi Komputer, 2024)
General elections are a means for the people to show that they have sovereignty. This concept implies that the people are the highest power holders in the country and they themselves determine the form and way the government is run. The implementation of regional head elections also reflects this understanding. In general, general elections aim to ensure that the transfer of government power occurs peacefully, regularly, and in accordance with the mechanisms guaranteed and regulated by the constitution. Political culture is a system of values ​​and beliefs held by a society. However, each element of society has a different political culture, for example between society and its elites. It is necessary to develop a political-cultural character where